Endocervicosis of the Bladder: Report of a Case and Review of the Current Literature - Heretis, John (e-Century Publishing Corporation, 2008)
An important variety of metaplastic lesions of the urinary bladder have been reported in the medical literature up to date. Among those of Müllerian origin, endocervicosis is the most infrequent. We report a 67 years old woman who presented with a history of left flank pain and dysuria for the past 2 months. Imaging studies revealed a solid mass in the posterior bladder wall protruding into the lumen. Transurethral resection of the lesion was performed. Both pathologic examination and immunohistochemistry confirmed the diagnosis of endocervicosis. The patient was monitored with 6 months interval follow up and remains disease free 12 months post surgery.